“CHILD TRAFFICKING” AS THE EMBODIMENT OF MODERN SLAVERY IN INTERNATIONAL LAW REVIEW - Joko Setiyono; Aga Natalis (International Journal of Law Reconstruction, 2022)
The purpose of this research is to find out the implementation and actualization of international and domestic law regarding child trafficking, to find examples of multilateral international cooperation forms that have been created in the context of overcoming child trafficking, and to identify threats and solutions needed by the international community in the prevention of Child Trafficking. This research was legal research with a normative juridical approach with descriptive-analytical research specifications. Child trafficking is a form of human trafficking. This crime can be attributed to the existence and widespread of the concept of "modern slavery." Internationally and nationally, laws regarding the prevention of child trafficking and child protection have been created. Examples in the international spectrum are UNTOC Annex II: Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children, supplementing the United Nations Convention against Transnational Organized Crime, Convention on The Rights of the Child created by UNICEF, International Program on the Elimination of Child Labor (IPEC) by the ILO, the World Congress against the Commercial Sexual Exploitation of Children, and the Palermo Protocol. With evidence of the development of child trafficking with the influence of cyberspace and information technology, the international community's concern on this issue must also increase. This is needed in making effective policies, laws, and actions in overcoming the crime of child trafficking.